The relationship between aortic valve calcification and risk of ischemic stroke - H. Zarepour; H. Mozhdehipanah; R. Jahanbakhsh; M. Sayadnasiri (The Journal of Qazvin University of Medical Sciences, 2017)
Background: Although most previous studies did not confirm the relationship between aortic valve calcification (AVC) and ischemic stroke, there are some case reports about the importance of AVC in occurrence of ischemic stroke. Objective: To investigate the relationship between aortic valve calcification and risk of ischemic stroke. Methods: This case-control study includes 600 patients (300 cases and 300 controls) admitted at Qazvin’s Bu-Ali Hospital from April 2014 to February 2015. Cases were selected from acute ischemic stroke patients admitted to the hospital Emergency Department and the control group consisted of non-stroke patients referred to cardiology clinic. Two groups were matched for sex, age and other vascular risk factors. All participants underwent transthoracic echocardiography. AVC was scored according to scaling system proposed by previous studies. Demographic, clinical and laboratory characteristics of all participants were also collected and the relationship between these parameters and echocardiographic findings were analysed using dependent t and chi-squared tests. P<0.05 was considered significant. Findings: Mean age of participants was 65.12±12.41 years (46.2% man). In 153 of stoke patients (51%), AVC was detected but only 35 participants (17.7%) of control group showed this abnormality (P<0.001). In case and control groups, aortic insufficiency was 54.3% (n=163) and 18.3% (n=55) respectively (P<0.001). Left ventricular hypertrophy was also more frequent in stroke patients (41.8% vs. 20.7%, P<0.001). Other cardiovascular risk factors were more in the patients of case group. However, the difference wasn’t statistically significant between two groups. Conclusion: According to this study, AVC and aortic insufficiency are related to ischemic stroke occurrence. More studies are needed to confirm these findings.